2015
DOI: 10.1002/kin.20923
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Kinetic Mechanism for 2‐Bromo‐3,3,3‐trifluoropropene (2‐BTP) Flame Inhibition

Abstract: In this work, we report a detailed chemical kinetic mechanism to describe the flame inhibition chemistry of the fire-suppressant 2-bromo-3,3,3-trifluoropropene (2-BTP), under consideration as a replacement for CF 3 Br. Under some conditions, the effectiveness of 2-BTP is similar to that of CF 3 Br; however, like other potential halon replacements, it failed an U.S. Federal Aviation Authority (FAA) qualifying test for its use in cargo bays. Large overpressures are observed in that test and indicate an exothermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 195 publications
4
48
0
Order By: Relevance
“…This Br abstraction was not considered in the study by Chen et al [4], while Zhang et al [5] reported Br abstraction for 1-BTP with a high barrier 42.3 kca/mol. This is of great interest when one realizes that the C-Br bond is the weakest bond in 2-BTP [6,10]. It can be explained by the fact that the interaction between the nucleophilic OH and the electrophilic H is much stronger than that between OH and Br (halogens are normally nucleophilic).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This Br abstraction was not considered in the study by Chen et al [4], while Zhang et al [5] reported Br abstraction for 1-BTP with a high barrier 42.3 kca/mol. This is of great interest when one realizes that the C-Br bond is the weakest bond in 2-BTP [6,10]. It can be explained by the fact that the interaction between the nucleophilic OH and the electrophilic H is much stronger than that between OH and Br (halogens are normally nucleophilic).…”
Section: Resultsmentioning
confidence: 99%
“…A great amount of studies have been focused on the inhibition chemistry mechanism, minimum extinguishing concentration, and combustion enhancement/suppression of 2-BTP by using theoretical calculation, model simulation or experiment [5,6,7,8,9,10,11,12,13,14,15,16,17]. According to previous studies, 2-BTP was considered to have a similar suppression performance to CF 3 Br given that both molecules contain a bromine atom and a CF 3 group [7,11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations